2013
DOI: 10.1111/nuf.12047
|View full text |Cite
|
Sign up to set email alerts
|

Eating, Activity, and Supportive Environment (EASE) for Nursing Students

Abstract: The American Nursing Association launched a Healthy Nurse program in 2012, as healthy nurses are role models for a healthy nation. Updating nursing curriculum and active participation of students in weight management programs will promote their own health and positive role modeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…A second important finding was that although the participants reported overall good scores on the SARMHEP, 64% of the sample was either overweight or obese based on a selfreport of height and weight. These findings were consistent with several studies reporting overweight and obesity ranging from 27 to 74% (Blake & Harrison, 2013;Esposito & Fitzpatrick, 2011;Roux et al, 2013). The self-report results of following a healthy diet are greater than the general population, however, not performing physical activity was much greater than the general population at almost 70% (CDC, 2009;CDC, 2014d).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A second important finding was that although the participants reported overall good scores on the SARMHEP, 64% of the sample was either overweight or obese based on a selfreport of height and weight. These findings were consistent with several studies reporting overweight and obesity ranging from 27 to 74% (Blake & Harrison, 2013;Esposito & Fitzpatrick, 2011;Roux et al, 2013). The self-report results of following a healthy diet are greater than the general population, however, not performing physical activity was much greater than the general population at almost 70% (CDC, 2009;CDC, 2014d).…”
Section: Discussionsupporting
confidence: 89%
“…In a study of 1,074 nurses, Slater, McElwee, Flemming, and McKenna, (2006) reported that smokers underestimated the risks of smoking (p < 0.001), the benefits of smoking cessation (p < 0.05) and were less likely to provide smoking education to their patients. This information was supported in six other studies (Beletsioti-Stika & Scriven, 2006;Hensel, 2008;Movsisyan et al, 2012;Roux et al, 2013;Willaing, Jorgensen, & Iversen, 2003;Willaing & Ladelund, 2004).…”
Section: Nurses and Health Promotionsupporting
confidence: 62%
See 1 more Smart Citation
“…Most authors referred to weight management and healthy eating when considering self-care (Connolly et al, 1997, Denehy, 2008, Hicks et al, 2008, Rush et al, 2010, Connolly et al, 2013, Roux et al, 2014, Blake and Patterson, 2015. Others considered self-care to include smoking cessation or being nonsmokers ( Connolly et al, 1997, Halcomb, 2005, Dunkley and Ward, 2005, Beletsioti-Stika and Scriven, 2006, Dao Thi Minh et al, 2008, Moxham et al, 2013.…”
Section: Defining Attributesmentioning
confidence: 99%
“…Nurses being role models in behaviours such as physical exercise might equip students to cope with stressors of the profession (Malik et al 2011). Inspiring behaviour change in the general public was viewed a consequence of nurses being healthy role models by many authors (Dalton and Swenson, 1986, Shriver and Scott-Stiles, 2000, Merrill et al, 2010, Moxham et al, 2013, Eggertson, 2013Roux et al, 2014. However, some considered the expectation to be healthy role models an added burden, which may create stress for some (Rush et al, 2005;Pollard 2005;Blake and Patterson, 2015).…”
Section: Consequencesmentioning
confidence: 99%